DIVESTITURE POST MERGERS AND ACQUISITIONS IN INDIA – REASONS AND MODEL TO PREDICT - Singh, Aditya Pratap; Singh, Archana; Maheshwari, Girish Chandra (Applied Studies in Agribusiness and Commerce, 2025)
Divestitures post-acquisition are a common occurrence yet the jury is still out on whether they represent correction of prior mistakes or are a restructuring tool to improve performance in the hands of managers evaluating overall portfolio of assets. We take a sample of 1,344 deals buy Indian public listed buyers from 2000 to 2020 of which 13% were followed by a divestiture to create models to predict if an acquisition is likely to be followed by a divestiture or not using logistic regression and discriminant analysis. Our model is more than 75% accurate in its prediction even when tested on unselected data (new data for the model). We find support for portfolio theory and reject the correction of prior mistakes theory to explain post-acquisition divestitures. We support the theory that financial constraints leads to post acquisition divestiture. We also support the theory on indigestion that post acquisition divestitures are due to cookie-jar problem where buyers are finding it difficult to integrate. Increased volatility and poor mean stock price returns both contribute to conditions leading to such divestitures. The model constructed is useful for shareholders and other stakeholders to predict whether a divestiture will follow an acquisition or not. Managers can also use the model to predict eventual outcome of their acquisition decisions.